2014
DOI: 10.5539/ijms.v6n1p168
|View full text |Cite
|
Sign up to set email alerts
|

An AHP Approach for Ranking Critical Success Factors of Customers Experience in Iranian Banks from Managers’ Viewpoint

Abstract: Nowadays, customer experience is considered as a critical factor in growth cycle of each business. These days only those organizations that their main focus is fulfilling customer's demands and desires with maximum quality can be succeed. The main purpose of this study is identifying and prioritizing critical success factors from perspective of bank's managers and experts. Considering these factors as key success factors can improve customer experience in banking services and help the banks to provide more fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The meaning of each of the values of the scale is presented in Table 3. The feedback questionnaires from professionals were estimated using the consistency ratio (CR) to ensure their reliability and validity (Lee et al, 2011;Haery, Ghorbani and Farahmand, 2014). Finally, a factor analysis was conducted to derive the interrelationships among the hindrance factors.…”
Section: Methodsmentioning
confidence: 99%
“…The meaning of each of the values of the scale is presented in Table 3. The feedback questionnaires from professionals were estimated using the consistency ratio (CR) to ensure their reliability and validity (Lee et al, 2011;Haery, Ghorbani and Farahmand, 2014). Finally, a factor analysis was conducted to derive the interrelationships among the hindrance factors.…”
Section: Methodsmentioning
confidence: 99%
“…This method can be used in the banking industry to assess service quality while also determining which service quality has the most impact on the services and requires the most ISSN: 2088-8708  How analytical hierarchy process prioritizing internet banking influencing factors? … (Khairi Azhar Aziz) 6649 work to provide [27]. As a result, a variety of decision-related problems could be solved using this decision support technique.…”
Section: Methodsmentioning
confidence: 99%
“…Importance of score variable By using this AHP technique, this research will attempt to show the internet banking adoption to be rank based on the identified of factors. This technique can be applied in banking environment to evaluating on their service quality and the same time to identify which of service quality requires most the efforts and impact to the services and fulfill customer satisfaction, Haery et al (2014). AHP also allow the quantitative and qualitative in to the similar of decision-making technique, which is by giving an eliciting, recording, discussing and evaluate elements for a decision, Miran (2017).…”
Section: Figure 1 Hierarchical Tree Of Ahp Processmentioning
confidence: 99%